DIRECTION OF THE ECONOMIC POLICY OF DEVELOPMENT OF INDONESIAN SPATIAL AND REGION - Bono Prambudi (FEB Universitas Sultan Ageng Tirtayasa, 2018)
The step of accelerating and expanding economic development is one of the government's steps in connecting between the interests of the center and the regions that must synergize and aspire to be stated in the 1945 Constitution. Policies in the area of developing regional governance or relating to national level RTRW and supervision. Regarding the problems that occur from the regional level to the central level or more familiarly the urban level is a crucial problem that is difficult to solve with a very short time.Keywords: Development, Policy and Spatial Planning